Network Security - Huang, Scott C.-H.; MacCallum, David; Du, Ding-Zhu.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
This volume highlights and addresses several key challenges in the area of Network Security. Covered is a comprehensive array of topics including secure metering, group key management, denial-of-service attacks, routing and intrusion detection and many more. The book contains eleven peer reviewed chapters, authored by prominent researchers from around the globe. Although the topics do not cover every aspect of network security, they do represent the most fundamental and practical techniques. Network Security should be of interest to researchers and network security experts in the field.
Secure Metering Schemes -- A Cryptographic Framework for the Controlled Release Of Certified Data -- Scalable Group Key Management for Secure Multicast: A Taxonomy and New Directions -- Web Forms and Untraceable DDoS Attacks -- Mechanical Verification of Cryptographic Protocols -- Routing Security in Ad Hoc Wireless Networks -- Insider Threat Assessment: Model, Analysis and Tool -- Toward Automated Intrusion Alert Analysis -- Conventional Cryptographic Primitives -- Efficient Trapdoor-Based Client Puzzle Against DoS Attacks -- Attacks and Countermeasures in Sensor Networks: A Survey.
Keywords: Computer science; Computer communication systems; Special purpose computers; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computer Science; Computer Communication Networks; Coding and Information Theory; Data Structures, Cryptology and Information Theory; Special Purpose and Application-Based Systems; Data Encryption; Electronic books